Abstraction in Pottery of the Pre-Writing Era - Iraq and Egypt A comparative analytical study (Journal of the College of Basic Education, 2022)
Civilizations from the first ages of human existence are measured by two main aspects, namely the pottery finds and the decorative symbols on their surfaces, through which it is possible to understand the depth of development of a civilization, and the pottery paintings in Iraq and Egypt created a distinctive thought and a pure effort that was able to convey the skill and the intellectual and aesthetic capacity of societies at the time, which indicates awareness A special and civilized development drawn by the vocabulary by its realistic existence sometimes and its abstractions at other time.Hence, there were numerous critical writings that dealt with these ancient arts through the problems of investigation and study of them and their stages of development and explorations, so that the bulk of them were transformed by the impact of the social and environmental relations prevailing at the time, which led to changing the researchers' perceptions and altering the images of research experiences and gave artistic and cultural products and artistic knowledge methods. And forms that the arts did not know except after passing through civilizations and their arts, and by that we mean the arts of formation in its total form and the arts of pottery in particular. Hence, it must be emphasized that the arts of pottery despite it being a historical practice in which the factors of "expansion" appear in concepts, theorizing and creativity in the traditional sense. There have emerged many problems, which is the mixing of the traditional rules represented by the random processes of ancient arts with their combinations and names, and those who prefer to allow things to take their natural paths to occur, including the drawings added to pottery vessels or sculptural forms that involve the emergence of a new category with historical meanings that have become empowered. In making it a "refraction" of the old and a shift through it towards the arts of modernity and beyond, especially the abstract concepts in which everything has become tilted at the level of contemporaneity and synchronization. This is what called the researcher to go into depth in this study to uncover the secrets of human thought and monitor the history of these societies.The research contained four chapters, of which the first chapter included a procedural framework for the research that included the research problem, the goal of the research and its importance, while defining the most important terms. The second chapter included three topics, the first of which dealt with abstraction as a concept, and the second topic the intellectual vision influencing art in ancient Iraq and the third topic the intellectual vision influencing Ancient Egyptian art. The third chapter contained the research procedures and analysis of its samples. The fourth and final chapter included mentioning the findings of the researcher. The following results appeared to the researcher:Ancient civilizations shared their use of making pottery and then porcelain in requirements of utilitarian and aesthetic requirements.The abstraction of forms in ancient Iraq depends on simulating a fixed idea that refers to life and permanence with great interest, reducing the functional value of the immediate and raising the aesthetic value of the product.The implementation of the ancient Egyptian pottery adopted the functional requirement, which reduced the spirituality of the mechanism of the spiritual intellectual discourse of the decree, and settled for assigning an aesthetic and performance function at the same time.